2009
DOI: 10.1021/nn9004268
|View full text |Cite
|
Sign up to set email alerts
|

Energy Gaps in Supramolecular Functionalized Graphene Nanoribbons

Abstract: The electronic structure characteristics of supramolecular functionalization of graphene nanoribbons with π-conjugated polymers are investigated using first-principles density functional theory. Noncovalent polymer functionalization leads to distinct changes in the electronic properties, particularly the band gaps of metallic and semimetallic graphene nanoribbons. A detailed analysis of band alignments reveals a profound level hybridization for ribbons with various shaped edges and spin density waves near the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 22 publications
(67 reference statements)
1
40
0
1
Order By: Relevance
“…Force-field-based molecular mechanics and density functional theory (DFT) calculations have shown that PETI-330 can wrap and form charge transfer complexes with carbon nanotubes providing a driving force for dispersion [28]. This result is qualitatively consistent with the study of other systems conducted by the same authors, such as a helical assembly of flavin interacting with carbon nanotubes [29] or polymers interacting with carbon nanotubes and graphene nanoribbons [30]. The results presented here indicated that some threshold of energy was required to attain homogeneous dispersion and distribution.…”
Section: Resultssupporting
confidence: 76%
“…Force-field-based molecular mechanics and density functional theory (DFT) calculations have shown that PETI-330 can wrap and form charge transfer complexes with carbon nanotubes providing a driving force for dispersion [28]. This result is qualitatively consistent with the study of other systems conducted by the same authors, such as a helical assembly of flavin interacting with carbon nanotubes [29] or polymers interacting with carbon nanotubes and graphene nanoribbons [30]. The results presented here indicated that some threshold of energy was required to attain homogeneous dispersion and distribution.…”
Section: Resultssupporting
confidence: 76%
“…One-dimensional graphene nanoribbons have attracted considerable attention in the fields of chemistry, materials science and physics12345678, and various studies on electronic91011, transport1213141516, and magnetic1718 properties have been conducted. The electronic properties of these nanoribbons are dominated by the edge structure, ribbon width1920, and bulk defects21.…”
mentioning
confidence: 99%
“…The electronic properties of silicene nanoribbons are dependent on the structural size and chirality. Via assistances of recent investigations [2326], the ZSiNRs exhibit rich electronic transport, magnetic properties, and may be applied in spintronic nanodevices potentially [2732]. In particular, electronic transport properties of the SiNRs are vital in electronic industry [3336].…”
Section: Introductionmentioning
confidence: 99%